2022
DOI: 10.3390/ijerph19074006
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Iron Levels in Autism Spectrum Disorders vs. Other Neurodevelopmental Disorders: Preliminary Data

Abstract: Autism Spectrum Disorder (ASD) is characterized by deficits in social skills and specific behaviors and interests. Among other environmental factors, iron may play a role in the development of ASD. The aim of this study is to compare the iron status of children with ASD with that of children affected by neurodevelopmental disorders other than ASD (OND). A total of 167 patients were enrolled, including 93 children with ASD and 74 children with OND. In the two groups, we determined ferritin, iron, transferrin, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In the DEG analysis, erythrocyte differentiation, erythrocyterelated disorders, and heme metabolism were enriched in children with ASD, and our clinical data from routine blood tests validated the significant changes in erythrocyte-related parameters (RBC, HCT, MCH, RDW-CV, and MCHC) in ASD patients. Erythrocyte parameters can reflect iron status (61), and thus the results presented above imply that abnormalities in iron metabolism affect the course of ASD, as reported in previous studies (62,63). ALAS2 (64, 65), SLC4A1 (66), AHSP (67), EPB42 (68), and GMPR (69) were identified as ASD hub genes, and these are associated with erythrocytes, especially with regard to changes in hemoglobin, which are closely related to iron metabolism.…”
Section: Discussionsupporting
confidence: 66%
“…In the DEG analysis, erythrocyte differentiation, erythrocyterelated disorders, and heme metabolism were enriched in children with ASD, and our clinical data from routine blood tests validated the significant changes in erythrocyte-related parameters (RBC, HCT, MCH, RDW-CV, and MCHC) in ASD patients. Erythrocyte parameters can reflect iron status (61), and thus the results presented above imply that abnormalities in iron metabolism affect the course of ASD, as reported in previous studies (62,63). ALAS2 (64, 65), SLC4A1 (66), AHSP (67), EPB42 (68), and GMPR (69) were identified as ASD hub genes, and these are associated with erythrocytes, especially with regard to changes in hemoglobin, which are closely related to iron metabolism.…”
Section: Discussionsupporting
confidence: 66%
“…A former clinical study indicated that 93 children with ASD had lower ferritin and higher mean corpuscular volume (MCV value) compared to 74 children with no neurodevelopmental disorders other than ASD [ 66 ]. The ASD gruop showed significantly higher MCV values due to a deficiency of vitamin B12 and folic acid.…”
Section: Iron Signaling and Asdmentioning
confidence: 99%
“…The ASD gruop showed significantly higher MCV values due to a deficiency of vitamin B12 and folic acid. Folic acid is essential for the correct synthesis of red blood cells [ 66 ]. Vitamin B12 is an essential component for DNA synthesis, and vitamin B12 deficiency causes neurologic and psychiatric symptoms, such as motor dysfunction, sensory and memory deficits, and cognitive impairment.…”
Section: Iron Signaling and Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…According to existing research, brain iron is closely related to neurological diseases ( 49 , 51 , 52 ). In ADHD and RLS, the same is true.…”
Section: Discussionmentioning
confidence: 99%